How often and when Fisher syndrome is overlapped by Guillain‐Barré syndrome or Bickerstaff brainstem encephalitis?. (11th March 2016) - Sekiguchi, Y.; Mori, M.; Misawa, S.; Sawai, S.; Yuki, N.; Beppu, M.; Kuwabara, S.
Abstract : Background and purpose: Fisher syndrome (FS) may overlap with Guillain–Barré syndrome (GBS), in particular the pharyngeal–cervical–brachial variant form (PCB‐GBS), or Bickerstaff brainstem encephalitis (BBE). Our aim was to elucidate the frequency of this overlap and the patterns of clinical progression in patients with FS. Methods: Sixty consecutive patients with FS were studied. FS/PCB‐GBS was diagnosed when the patients developed pharyngeal, cervical and/or brachial weakness. Patients with flaccid tetraparesis were diagnosed as having FS/conventional GBS. FS/BBE was defined as the development of consciousness disturbances. Results: All 60 patients initially developed the FS clinical triad alone (pure FS). Of these, 30 (50%) patients had pure FS throughout their course, whereas the remaining 50% of patients showed an overlap: PCB‐GBS in 14 (23%) patients, conventional GBS in nine (15%) patients and BBE in seven (12%) patients. The median (range) durations from FS onset to progression to FS/PCB‐GBS, FS/GBS or FS/BBE were 5 (1–7), 3 (1–4) and 3 (1–5) days, respectively. Patients with overlap syndromes more frequently received immune‐modulating treatment, and the outcomes were generally favourable. The frequencies of positivity for anti‐GQ1b, GT1a, GD1a, GD1b, GalNAc‐GD1a and GM1 antibodies were not significantly different amongst the four groups. Conclusions: Of the patients with pure FS, 50% later developed an overlap with PCB‐GBS, conventional GBS or BBE. The overlap occurred within 7 days of FS onset; thus, physicians should pay attention to the possible development of this overlap during the first week after FS onset.